Association of White Blood Cell Count With Clinical Outcome Independent of Treatment With Alteplase in Acute Ischemic Stroke - Barow, Ewgenia; Quandt, Fanny; Cheng, Bastian; Gelderblom, Mathias; Jensen, Märit; Königsberg, Alina; Boutitie, Florent; Nighoghossian, Norbert; Ebinger, Martin; Endres, Matthias; Fiebach, Jochen B.; Thijs, Vincent; et al. (Frontiers in Neurology, 2022)
Introduction: Higher white blood cell (WBC) count is associated with poor functional outcome in acute ischemic stroke. However, little is known whether the association is modified by treatment with intravenous alteplase. Methods: WAKE-UP was a randomized controlled trial of efficacy and safety of magnetic resonance imaging [MRI]-based thrombolysis in unknown onset stroke. WBC count was measured on admission and again at 22-36 hours after randomization to treatment (follow-up). Favorable outcome was defined by a score of 0 or 1 on the modified Rankin Scale (mRS) at 90 days after stroke. Further outcomes were stroke volume and any hemorrhagic transformation (HT) assessed on follow up CT or MRI. Multiple logistic regression analysis was used to assess the association between outcome and WBC count and treatment group. Results: Of 503 randomized patients, WBC count and baseline parameters were available in 437 patients (µ=64.7 years, 35.2% female) on admission and 355 patients (µ=65.1 years, 34.1% female) on follow-up. Median WBC count on admission was 7.6 x 109 g/l (interquartile range, IQR, 6.1 – 9.4 x 109 g/l) and 8.2 x 109 g/l (IQR, 6.7 – 9.7 x 109 g/l) on follow-up. Both, higher WBC count on admission and on follow-up was associated with lower odds of favorable outcome, adjusted for age, NIH Stroke Scale score, temperature and treatment (alteplase vs. placebo, adjusted odds ratio, aOR 0.85, 95% confidence interval [CI] 0.78-0.94 and aOR 0.88, 95% CI 0.79-0.97). No interaction of WBC count and treatment group was observed (p=0.11). Furthermore, WBC count on admission and follow-up was significantly associated with HT (aOR 1.14, 95%CI 1.05-1.24 and aOR 1.13, 95%CI 1.00-1.26). Finally, WBC count on follow-up was associated with larger stroke volume (aOR 2.57, 95% CI 1.08-6.07). Conclusions: Higher WBC count is associated with unfavorable outcome, an increased risk of HT, and larger stroke volume, independent of treatment with alteplase. Whether immunomodulatory manipulation of WBC count improves stroke outcome needs to be tested. ClinicalTrials.gov identifier NCT01525290.